Cloud Computing in Business - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (International Journal on Human-Computing Studies, 2023)
Businesses need the means to enhance their efficiency, productivity, and overall performance in today’s modern competitive climate, and cloud technology offers a flexible means of doing that. Cloud computing is the delivery of computing services including servers, storage, databases, networking, software, analytics, and intelligence over the Internet (the cloud or virtual space). This implies that businesses will move their whole operations to the cloud. Many businesses are not willing to make this change because it is an expensive and sometimes complicated operation. The cloud can help a business save money, become more agile, and operate more efficiently. This paper provides an introduction on cloud computing for businesses. It identifies the strengths, weaknesses, opportunities, and threats for the cloud computing use in the business environment.